Application of the herbal chemical marker ranking system (Herb MaRS) to the standardization of herbal raw materials: a case study - Kaggwa, Bruhan; Anywar, Godwin; Munanura, Edson Ireeta; Wangalwa, Raphael; Kyeyune, Henry; Okella, Hedmon; Kamba, Fadhiru Pakoyo; Engeu, Ogwang Patrick (BMC Complementary Medicine and Therapies, 2023)
Introduction: Phytochemical standardization of herbal materials involves establishing consistent levels of one or more active ingredients or markers. It ensures the authenticity and quality of herbal materials, extracts, and their products. This research aimed to apply the herbal chemical marker ranking system (Herb MaRS) originally proposed for quality assurance of complex herbal products to establish markers for controlling the quality of herbal raw materials. Methods: The assessment of compounds for suitability as markers was based on the Herb MaRS, with minor modifications as follows: for more objective scoring, evidence of biological activity of the potential marker compound(s) was determined at three levels based on the number of symptoms of the disease condition a compound can treat or alleviate: (i) one symptom (1 point), two symptoms (2 points), and 3 or more symptoms (3 points). The reported concentrations of the compounds were also scored as follows: concentration not determined (0 points), concentration ≥ 5 ppm (1 point), concentration ≥ 50 ppm (2 points) and availability of analytical standards (1 point). Finally, the compounds were scored for the availability of an analytical method (1 point). The compounds were scored from 0 to 8, where 8 indicated the most suitable chemical marker. Results: The selected markers were as follows: aromadendrine, α-terpineol, globulol, and 1,8-cineol (in Eucalyptus globulus Labill. ) ; aloin, aloe emodin, acemannan (in Aloe barbadensis (L.) Burm.f. ), lupeol, lupenone, betulinic acid, betulin, and catechin (in Albizia coriaria Oliv.); mangiferin, catechin, quercetin, and gallic acid (in Mangifera indica L.); polygodial (in Warburgia ugandensis Sprague); azadirachtin, nimbin, nimbidin (in Azadirachta indica A. Juss. ); and 6,8,10-gingerols, and 6-shogaol (in Zingiber officinalis Roscoe). Conclusions: Herb MaRS can be efficiently applied to select marker compounds for quality control of herbal materials. However, for herbs whose phytochemicals have not been sufficiently researched, it is difficult to establish evidence of activity, and there are no analytical standards and/or methods; this is the case for plants exclusively used in Africa. The markers identified should be incorporated into chromatographic fingerprints, their quantitative methods developed, and evaluated for applicability at the various stages of the production chain of herbal medicines; then, they can be included in future local plant monographs. There is also a need to build local capacity to isolate marker compounds, particularly those that are not sold by current vendors.
Keywords: Markers; Phytochemical standardization; Quality control; Herbal materials; Herbal products